LabVIEW design for electronic control of microfluidic chip - Tan, Boon Huat (Nanyang Technological University, 2022)
Microfluidics refers to the manipulation of liquid in small quantities typically in the microliter range. This manipulation is highly valuable in many industries as less volume of reactant is required to produce the experiment results or fabrication. Fluids tend to behave and react differently on the micrometric scale in the experiment and are greatly affected by the ability to maintain a flow without interruption. Even in a controlled environment where most chemical and physical properties of liquid can be ad mistered, the ability of a microfluidic system to control fluid with high precision and the capability to reduce labour-intensive work is still highly sought after.